Iluzja i deziluzja. Dążenie do wolności pokolenia ’68 i jego konsekwencje na przykładzie próby odnalezienia siebie, dziecka tego pokolenia, w powieści Zoe Jenny pt. „Kwietny pył” - Wawrzynek, Karin (Studia Europaea Gnesnensia, 2016)
In this article, the example of a child of the ’68 generation, in this case Jo, a protagonist in „The Pollenroom” by the Swiss author Zoë Jenny, serves to illustrate the conflict between the ’85 generation and the ’68 generation and its serious consequences, which concern the urge of freedom, the ideals, the anti-authoritarian view of life, women´s movement as well as the overcoming and disintegration of traditional conventions and structures of society. The characteristic traits of the ’68 generation have fatal repercussions for its descendants. The author seeks to show how difficult it could be to live in this estranged world and find oneself for a child abandoned by its parents who pursued their ideals and the fulfilment of their dreams.